Cultural and Economic Influences on Healthcare Choices: A Narrative Review - Baculu, Eka Prasetya (Yayasan Sinergi Kawula Muda, 2024)
Healthcare preferences in urban and rural communities are shaped by a range of economic, cultural, and infrastructural factors, influencing access to traditional and modern medicine. This study examines the determinants of healthcare choices, highlighting disparities in accessibility and healthcare utilization. A systematic review methodology was employed, analyzing peer-reviewed literature from databases such as PubMed, Scopus, and Google Scholar. Inclusion criteria focused on studies addressing community perceptions, healthcare access, and integrative healthcare models. Findings indicate that rural communities continue to rely on traditional medicine due to accessibility and cultural significance, while urban populations predominantly utilize modern medical services due to better infrastructure and preventive healthcare access. Financial constraints and inadequate healthcare infrastructure were identified as key barriers limiting modern healthcare accessibility in rural areas. The study also highlights the increasing recognition of integrative healthcare models, demonstrating their potential in addressing healthcare disparities by combining traditional and modern practices. The findings underscore the need for policy interventions to enhance healthcare equity, including government-led initiatives to integrate traditional medicine into national healthcare frameworks, investments in rural healthcare infrastructure, and the promotion of telemedicine solutions. Future research should explore the effectiveness of integrative models in improving health outcomes and investigate scalable digital healthcare solutions for rural populations. This study contributes to the growing discourse on healthcare accessibility, emphasizing the need for culturally inclusive and equitable healthcare systems.